Educação a distância online: potencialidades para a formação de professores que ensinam matemática - Paulin, Juliana França Viol [UNESP] (2015)
This study aims to understand the potentialities of online Distance Learning (DL) on the constitution of spaces that promote the teacher education processes of Math teachers. In order to meet this goal, we developed this research, guided by the following investigative question: How does online DL show itself in relation to the teacher education processes of Math teachers? Thus, we guided ourselves according to the qualitative perspective of metaanalysis and incorporated data from three practical contexts of research - Theses and Dissertations; Scientific Articles from SIPEM; Interviews with Teachers/Researches - that were analyzed following some procedures, based on some concepts of Content Analysis. At first, we developed a critical mapping of the Theses, Dissertations, and Articles that showed six themed axes representing the research's trends on the investigated theme: Didactic and pedagogical aspects of online DL; Epistemological aspects of online DL; Public Policies for Distance Teacher Education; Teaching Practices on the online DL context; Education Process of Math Teachers; and Implementation Processes for Distance Teacher Education Courses. In a second stage, we proceeded in the search for the potentialities of online DL for the constitution of formative spaces along with the three practical contexts of research, which led us to the identification of four categories of analysis: The Constitution of the teaching profession on online DL; The teaching and learning processes in Distance Teacher Education Courses; The Distance Teacher Education process; and The Epistemology of online DL for Education Teachers. These categories were analyzed in light of theoretical and methodological contributions about DL and Teacher Education, and directed us to a possible meta-understanding of the investigated subject. The research shows that the aspects highlighted as potentialities of online DL for the constitution of formative spaces...